Effect of dietary zinc source, zinc concentration, and exogenous phytase on intestinal phytate degradation products, bone mineralization, and zinc status of broiler chickens - Hanna Philippi; Vera Sommerfeld; Oluyinka A. Olukosi; Wilhelm Windisch; Alessandra Monteiro; Markus Rodehutscord (Poultry Science, 2023)
ABSTRACT: This study aimed to determine the effect of Zn source and dietary level on intestinal myo-inositol hexakisphosphate (InsP6) disappearance, intestinal accumulation of lower InsP and myo-inositol (MI), prececal mineral digestibility, bone mineralization, and Zn status of broilers without and with exogenous phytase in the feed. Male Ross 308 broilers were allocated in groups of 10 to 8 treatments with 8 pens each. Experimental diets were fed from d 7 to d 28 and contained 33 mg/kg dry matter plant-intrinsic Zn. Experimental factors were phytase supplementation (0 or 750 FTU/kg) and Zn source (none [0 mg/kg Zn], Zn-sulfate [30 mg/kg Zn], Zn-oxide [30 mg/kg Zn]). Additional treatments with 90 mg/kg Zn as Zn-sulfate or Zn-oxide and phytase were included to test the effect of Zn level. No Zn source or Zn level effects were observed for ADG, feed conversion ratio, prececal P digestibility, intestinal InsP6 disappearance, and bone ash concentration. However, those measurements were increased by exogenous phytase (P < 0.001), except the feed conversion ratio, which was decreased (P < 0.001). Ileal MI concentrations were affected by phytase × Zn source interaction (P < 0.030). Birds receiving exogenous phytase and Zn supplementation had the highest MI concentrations regardless of exogenous Zn source, whereas MI concentrations were intermediate for birds receiving exogenous phytase only. Exogenous phytase and exogenous Zn source increased the Zn concentration in bone and blood of broilers (P < 0.001). In conclusion, measures of exogenous phytase efficacy were not affected by phytase × Zn source interaction. Further studies are needed to rule out an effect from Zn sources other than those tested in this study and to investigate the effect of Zn supplementation on endogenous phosphatases. The missing effect of increasing Zn supplementation from 30 to 90 mg/kg in phytase-supplemented diets gives reason to reconsider the Zn supplementation level used by the industry.